Impatiens kanchigandhiana, a new name for Impatiens nasuta H.Perrier (Balsaminaceae) - Rasingam, Ladan; Karthigeyan, K.; Gogoi, Rajib (Phytotaxa, 2016)
The genus Impatiens Linnaeus (1753: 937) is distributed mostly in the tropical and subtropical regions of the Old World as well as in the northern temperate regions with more than 1,000 species (Janssens et al. 2006, Jyosna & Janarthanam 2011). During the taxonomic study of the genus Impatiens in India (Gogoi & Borah 2015, Gogoi & Arisdason 2016, Gogoi et al. 2016), we find that the name Impatiens nasuta Perrier de la Bâthie (1949: 14), a species native to Tsaratanana hills of Madagascar, is a later homonym of Impatiens nasuta Hooker (1908: 263) from China. Impatiens nasuta H.Perrier differs from I. nasuta Hook.f. in its smaller, suberect, less than 30 cm tall habit, leaves elliptic, smaller, coriaceous and flowers without an annular spur. According to the Arts. 6.11, 53.1 of the ICN (McNeill et al. 2012), a new name is proposed here for the later homonym Impatiens nasuta H.Perrier.